2018
DOI: 10.1021/acssuschemeng.7b04518
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant E. coli Cellulases, β-Glucosidase, and Polygalacturonase Convert a Citrus Processing Waste into Biofuel Precursors

Abstract: Molecular and biochemical characterization of lignocellulohydrolases cel12B, cel8C, β-glucosidase, and peh28 from Pectobacterium carotovorum subsp. carotovorum (Pcc) expressed in Escherichia coli (E. coli) was reported in a previous work. The current preliminary study investigates the enzymes’ catalytic performance on Rio-Red grapefruit processing waste (GPW) conversion which can lead to the development of low-cost and effective strategies with strain engineering and/or modified catalysts for production of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In an optimized buffer solution, the enzymes were suspended and exposed with pure form of known carbon substrates. The carboxymethyl cellulose (CMC), Avicel, and p-nitrophenyl-D-glucopyranoside (pNPG) are examples of carbon source that are used to detect the activity of endoglucanase, exoglucanase and β-glucosidase respectively [14]. Enzyme activities are examined using assays that measure the amount of reducing sugars produced by the processes.…”
Section: Heterologous Expression Of Recombinant Cellulasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In an optimized buffer solution, the enzymes were suspended and exposed with pure form of known carbon substrates. The carboxymethyl cellulose (CMC), Avicel, and p-nitrophenyl-D-glucopyranoside (pNPG) are examples of carbon source that are used to detect the activity of endoglucanase, exoglucanase and β-glucosidase respectively [14]. Enzyme activities are examined using assays that measure the amount of reducing sugars produced by the processes.…”
Section: Heterologous Expression Of Recombinant Cellulasesmentioning
confidence: 99%
“…The expanding range of choice to include Oil Palm Empty Fruit Bunch (OPEFB) [4]; [15] as carbon source for cellulase production has promised a new gateway through which the accumulation of palm oil industrial wastes in Malaysia could be utilized fully. Elsewhere, where grapefruit processing waste (GPW) is common, the study by Ibrahim et al [14]; [17] demonstrated the role of cellulases harvested from E. coli in converting the mentioned waste into biofuel precursors. Their study had detected a considerable amount of reducing sugars (i.e.…”
Section: Heterologous Expression Of Recombinant Cellulasesmentioning
confidence: 99%
“…A range of biotechnological applications have recently been proposed for the valorization of orange juice processing waste, including the recovery of high added-value products like natural antioxidants, essential oils and pectin [4,5], the manufacturing of absorbent material [6] and the production of bioethanol and biomethane [7][8][9]. Regarding enzyme technology, the use of citrus processing waste as bioresource for cellulases and pectinases has also been explored [10] for potential applications in food technology, solid-state fermentation and energy recovery [11,12]. In addition, the production of xylanases and the investigation of their potential uses in food and feed technologies, the pulp and paper industries, and biofuel production are of high interest [13].…”
Section: Introductionmentioning
confidence: 99%